The Effects of Preprocessing and Drying Methods on the Quality of a Nutritious Dried Soup Product Derived from Purple Sweet Potatoes and Chinese Kale Leaves. - PICHAIYONGVONGDEE, SUWANNA; RATTANAPUN, BOONYAKRIT; SINGKONG, WACHIRA; CHYSIRICHOTE, TEERANUCH; RASAMIPAIBOON, NUJIRA; PHONGSOPA, JIRAPORN (Current Research in Nutrition & Food Science, 2025)
In general, most traditional cream soups are high in carbohydrates and low in calcium, fiber, and phytochemicals, which reduces their nutritional value. Therefore, the development of purple sweet potato soup fortified with Chinese kale was important to enhance its nutritional value and address malnutrition. This innovative product combines the health benefits of purple sweet potato due to its antioxidant properties, while Chinese kale was a rich source of calcium and dietary fiber, making it a more nutritious and health-promoting food. This research investigated the effects of different pre-processing and drying methods on the physicochemical and cooking properties of freeze-dried soup products made from purple sweet potato (PP) and Chinese kale (CK). CK was blanched in 1% NaCl and 1% NaHCO3 solutions and then tray-drying and freeze-drying techniques were used. It was found that CK branched in 1% NaCl solution and freeze-dried retained significant levels of chlorophyll, calcium, fiber, and antioxidants. Steaming PP before drying increased the anthocyanin content more than boiling. Freeze-dried PP had a higher fiber content than tray-dried PP. Therefore, a soup using freeze-dried CK and PP was developed to develop a healthy purple sweet potato powder soup with three levels of CK supplemented (5, 10, and 15%). All formulas were sensory evaluated by quantitative descriptive analysis (QDA) by 10 food experts. It was found that the appropriate amount of additional freeze-dried CK of 10% could be determined. The ratio of PP-CK soup to hot water is 1:5 to achieve the most suitable taste, viscosity, mouthfeel, and overall acceptability. The soup is nutritionally rich, high in calcium, dietary fiber and antioxidants, making it an excellent choice for a healthy breakfast.